Willingness to participate in HIV-1 vaccine trials among young Thai men. Issue 5 (1st October 2000) - Jenkins, R A; Torugsa, K; Markowitz, L E; Mason, C J; Jamroentana, V; Brown, A E; Nitayaphan, S
Abstract : Objectives: Willingness to participate in HIV-1 vaccine trials and associated factors were investigated in a sample of 2670 Royal Thai Army conscripted recruits. Methods: Self administered questionnaires were used. Data were collected during the final visit of a longitudinal cohort study of HIV-1 epidemiology. Cross sectional analysis of data from this visit was performed. Results: 32% of the respondents reported they would "definitely" join an HIV-1 vaccine trial. Greater willingness was associated with perceived risk of HIV-1 infection and a desire to help Thai society, although tangible incentives and intentions to reduce condom use in a vaccine trial also were associated with increased willingness. Concerns about physical harm and anticipated social pressure from family not to join were the most substantial impediments to willingness. Concerns about "social harm" (for example, participation would give appearance of having AIDS virus, a partner might refuse sex) also appeared to inhibit interest in joining trials and approached significance. Conclusions: Willingness to participate was somewhat greater than in other investigations of non-injection drug user (IDU) cohorts in Thailand, with fewer concerns expressed about physical harm. Motivations appear to involve tradeoffs among perceived risk, anticipated social pressure, altruism, and tangible rewards. The absence of significant problems associated with vaccine trials to date, along with the presence of educational interventions in the study may help explain the lower level of concerns here relative to other Thai studies.